2001
DOI: 10.1007/s007950100008
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and molecular anatomy of gap junctions

Abstract: In animal tissues, most cells are connected via intercellular cytoplasmic channels called gap junctions. Various electron microscopy techniques have made a crucial contribution to our understanding of the function and structure of gap junction channels. Tracer studies and freeze-fracture replica observations indicate that the connexon, the unit gap junction channel, is a pair of hemichannels apposed in the narrow intercellular gap between neighboring cell membranes. Recent advances in cellular biology have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 12 publications
0
20
0
4
Order By: Relevance
“…6 Molecular studies have revealed more than 20 mammalian members of the connexin protein family. 7 Two gap junction proteins Connexin 43 (Cx43) and Connexin 50 (Cx50) have been identified in human corneal epithelium, while Cx43 gap junctions have also been detected in corneal stroma. 8,9 Corneal gap junctions mediate the intercellular transfer of ions and low molecular weight metabolites in basal epithelium and stroma through a complicated phosphorylation-induced mechanism of activation and thus, determine the cell metabolic synchrony and cooperation within 10,11 In the present study, we examined the expression of gap junction protein Cx43 in keratoconus, which is characterized by altered epithelial and stromal metabolism in the cornea, to unravel its potential role in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…6 Molecular studies have revealed more than 20 mammalian members of the connexin protein family. 7 Two gap junction proteins Connexin 43 (Cx43) and Connexin 50 (Cx50) have been identified in human corneal epithelium, while Cx43 gap junctions have also been detected in corneal stroma. 8,9 Corneal gap junctions mediate the intercellular transfer of ions and low molecular weight metabolites in basal epithelium and stroma through a complicated phosphorylation-induced mechanism of activation and thus, determine the cell metabolic synchrony and cooperation within 10,11 In the present study, we examined the expression of gap junction protein Cx43 in keratoconus, which is characterized by altered epithelial and stromal metabolism in the cornea, to unravel its potential role in the pathophysiology of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…7 In the inner ear, Cx26 plays a crucial role in the regulation of cochlear homeostasis and in the production of the endocochlear potential. 8 Therefore, mutations in the Cx26 gene cause a structural and functional defects in these gap junctions, leading to persistently high intracellular potassium concentration; this damages the mechanism that allows the quick response of ciliated cells to new auditory stimuli, consequently resulting in hearing loss. 9 Among the mutations in the Cx26 gene described so far, which cause DFNB1, a particular mutation and the first one described, the 35delG mutation accounts for most of the mutant alleles (60-85%) in the Mediterranean European population.…”
Section: Introductionmentioning
confidence: 99%
“…Cxs form a multigene family of at least 20 proteins that share a highly conserved sequence and topography throughout the phylogenetic scale (Richard, 2000;Willecke et al, 2002). However, the molecular weight, unitary conductance of the resulting channel, voltage dependency and tissue distribution differ between individual Cxs (Harris and Bevans, 2001;Shibata et al, 2001;Willecke et al, 2002). Studies of spontaneous Cx mutations and of transgenic mice featuring altered expression of selected Cxs have indicated that these proteins, and/or the intercellular communication that they permit, contribute to the in vivo homeostasis of several tissues (Kelsell et al, 2001b;Willecke et al, 2002).…”
Section: Introductionmentioning
confidence: 99%